A Temporal Sampling Basis for Visual Processing in Developmental Dyslexia - Archer, Kim; Pammer, Kristen; Vidyasagar, Trichur Raman (Frontiers in Human Neuroscience, 2020)
Knowledge of oscillatory entrainment and its fundamental role in cognitive and behavioral processing has increasingly been applied to research in the field of reading and developmental dyslexia. Growing evidence indicates that oscillatory entrainment to theta-frequency spoken language in the auditory domain, along with cross-frequency theta-gamma coupling, support phonological processing (i.e. cognitive encoding of linguistic knowledge gathered from speech) which is required for reading. This theory is called the temporal sampling framework (TSF) and can extend to developmental dyslexia, such that inadequate temporal sampling of speech-sounds in people with dyslexia results in poor theta oscillatory entrainment in the auditory domain, and thus a phonological processing deficit which hinders reading ability. We suggest that inadequate theta oscillations in the visual domain might account for the many magno-dorsal processing, oculomotor control and visual deficits seen in developmental dyslexia. We propose two possible models of a magno-dorsal visual correlate to the auditory TSF: 1) A direct correlate that involves “bottom-up” magnocellular oscillatory entrainment of the visual domain that occurs when magnocellular populations phase lock to theta-frequency fixations during reading; 2) an inverse correlate whereby attending to text triggers “top-down” beta/ low gamma signals from higher-order visual processing areas, thereby organizing magnocellular populations to synchronize to a theta frequency to drive the temporal control of oculomotor movements and capturing of letter images at a higher frequency.